2016
DOI: 10.1002/2016gl069936
|View full text |Cite
|
Sign up to set email alerts
|

Tropopause sharpening by data assimilation

Abstract: Data assimilation was recently suggested to smooth out the sharp gradients that characterize the tropopause inversion layer (TIL) in systems that did not assimilate TIL‐resolving observations. We investigate whether this effect is present in the ERA‐Interim reanalysis and the European Centre for Medium‐Range Weather Forecasts (ECMWF) operational forecast system (which assimilate high‐resolution observations) by analyzing the 4D‐Var increments and how the TIL is represented in their data assimilation systems. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…However, the meridional temperature gradients in the lowermost stratosphere are of low magnitude, so it is not clear why the RWP temperature anomalies maximize so close to the tropopause and not higher up. Pilch Kedzierski et al (2017) also reported wave amplitudes maximizing within a short height range close to the tropopause.…”
Section: Classical Rwp Examplementioning
confidence: 89%
See 2 more Smart Citations
“…However, the meridional temperature gradients in the lowermost stratosphere are of low magnitude, so it is not clear why the RWP temperature anomalies maximize so close to the tropopause and not higher up. Pilch Kedzierski et al (2017) also reported wave amplitudes maximizing within a short height range close to the tropopause.…”
Section: Classical Rwp Examplementioning
confidence: 89%
“…Alexander and Shepherd (2010) studied planetary wave activity in the Arctic and Antarctic lower and mid-stratosphere, while Shepherd and Tsuda (2008) studied planetary waves in the SH polar summer at 30 km height. Pilch Kedzierski et al (2017) used GNSS-RO to study extratropical tropopause modulation by waves, although only separating wave activity by timescale and propagation direction, without describing wave properties. Our study is a first attempt to describe RWP properties in the extratropics with the use of GNSS-RO.…”
Section: R Pilchmentioning
confidence: 99%
See 1 more Smart Citation
“…7 and 9 may be partially under-represented by GCMs. In fact, GCMs, reanalyses and forecast models are known to produce too smooth temperature gradients in the tropopause region (Gettelman et al, 2010;Hegglin et al, 2010;Birner et al, 2006;Pilch Kedzierski et al, 2016b). The tendency of forecast models of smoothing the tropopause with lead time (Gray et al, 2014) is partially compensated by diabatic and parameterized processes in the modelled RWPs (Saffin et al, 2017).…”
Section: The 2010 Moscow Heatwave Casementioning
confidence: 99%
“…Recent studies have shown that the TIL and the associated static stability enhancement occur at all latitudes, as revealed by satellite and ground‐based observations, as well as reanalysis data and model simulations (Grise et al, 2010; Gettelman et al, 2011; Zhang YH et al, 2015, 2019; Liu HL, 2017). The enhanced static stability above the tropopause is closely related to the wind shear and gravity waves (GWs) in this region (Liu HL, 2007, 2017; Sunilkumar et al, 2015, 2017; Zhang YH et al, 2015, 2019; Pilch Kedzierski et al, 2016). Through model simulations, Liu HL (2017) showed that large wind shears exist in the TIL region.…”
Section: Introductionmentioning
confidence: 99%